The effectiveness of Dekasan for prevention of postoperative complications after major bone surgeries - A Kalashnikov (Interdisciplinary Academy of Pain Medicine, 2021)
Antiseptic drug “Decasan” due to its bactericidal, fungicidal, viricidal and sporicidal action is a highly effective medicine for the prevention of postoperative complications in an orthopedic and trauma hospital. Its use can significantly reduce the frequency of complications, and thus reduces the need for systemic antibiotics and slows down the develop-ment of antibiotic resistance.